Sexual behaviour change in seronegative limbic encephalitis due to the involvement of the left amygdala - Varoglu, Asuman Orhan; Karatepe, Hasan Turan (Journal of the Pakistan Medical Association, 2022)
Limbic encephalitis (LE), a rare cause of encephalitis, generally presents with neuropsychiatric manifestations, memory deficits, seizures, and movement disorders. The case of a 41-year-old female patient with LE involving the left amygdala is presented. The patient was admitted to the emergency department with complaints of unconsciousness and seizures. Paraneoplastic and limbic markers were negative. This case was diagnosed as seronegative LE. Three to four months after the diagnosis, it was observed that her sexual preference changed to the female sex. No report has been published so far, concerning any case of LE associated with changes in sexual behaviour. The patient was treated with intravenous methylprednisolone (IVP) and triple antiepileptic therapy. After treatment, changes in sexual behaviour returned to the previous state. Keywords: limbic encephalitis, sexual behaviour, autoimmune encephalitis, paraneoplastic syndrome, left amygdala, homosexual.